การวิเคราะห์ลักษณะภัยแล้งและพื้นที่เสี่ยงด้านการเกษตรบริเวณภาคเหนือของประเทศไทยด้วยดัชนีภัยแล้งทางอุตุนิยมวิทยา - วรลักษณ์ ไก่งาม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The study of “Analysis of Drought Characteristics and Agricultural Risk Areas in Northern Thailand by Meteorological Drought Index” is the analysis of characteristics of the spatial and temporal of meteorological drought in northern Thailand, according to the meteorological region, during the years 1980 - 2017 (38 years) during the rainy season in Thailand. This study aimed to 1) analyze of characteristics of the spatial and temporal drought in northern Thailand, and 2) analyze the risk areas in agricultural land use areas in northern Thailand. The methodology of the first objective is to analyze of characteristics of the spatial and temporal drought in northern Thailand from 1980 - 2017 during the rainy season. First, check the efficiency of rainfall data, that used in the study, are gridded rainfall data from the Climatic Research Unit (CRU) with a spatial resolution of 0.5 ° x 0.5 °, compared with monthly rainfall data from 31 observation stations of the Thai Meteorological Department (TMD) in northern Thailand by analyzing the relationship between rainfall data both forms. The results of this study showed that the correlation coefficient between TMD’s monthly observed rainfall data and CRU’s gridded data is high with a range of 0.826 - 0.983 at the significance level of 0.01. Therefore, CRU’s gridded data is as effective as rainfall data from observation stations, which indicates that the CRU’s gridded data can be represented as the observation data. In this study used CRU’s gridded data instead of observation data. For the analysis of characteristics of the spatial and temporal drought, by analyzing the Standardized Precipitation Index (SPI) from CRU's precipitation gridded data covering the northern region. By calculating the SPI index in 2 different periods which is the 3-month SPI index (SPI3) and the 6-month SPI index (SPI6) to analyze the drought of the rainy season from May to October. It consists of analyzing the characteristics of the spatial and temporal of meteorological drought during the rainy season from analyzing the SPI3 of July (average of May - July), SPI3 of August (average of June - August), SPI3 of September (average of July - September), SPI3 of October (average of August - October) and drought throughout the rainy season from analyzing the SPI6 of October (average of May - October). This study focuses on severe drought to extreme drought (≤ -1.50), especially in the year of severe drought to extreme drought, representing more than 25% of the northern region. For the second Objective, analyze the risk areas in agricultural land use areas, by using the results from Objective 1 analysis together with agricultural land use data. The findings of this research found that meteorological drought from the analysis of the SPI3 of July found that there was severe drought to extreme drought areas, representing more than 25% of the northern region for 2 years, namely 1987 and 2015. In 2015, there was severe drought to extreme drought areas 97.10%, and there was drought risk area in the agricultural land use areas: extreme risk 82.456%, severe risk 12.943% of the agricultural land use area. The analysis of the SPI3 of August found that there was severe drought to extreme drought areas, representing more than 25% of the northern region for 3 years, namely 1982 1993 and 2015. In 2015, there was severe drought to extreme drought areas 77.28%, and there was drought risk area in the agricultural land use areas: extreme risk 46.07%, severe risk 22.908% of the agricultural land use area. The analysis of the SPI3 of September found that there was severe drought to extreme drought areas, representing more than 25% of the northern region for 3 years, namely 1986 1989 and 2015. In 2015, there was severe drought to extreme drought areas 46.44%, and there was drought risk area in the agricultural land use areas: extreme risk 4.232%, severe risk 42.932% of the agricultural land use area. The analysis of the SPI3 of October found that there was severe drought to extreme drought areas, representing more than 25% of the northern region for 5 years, namely 1981 1986 1998 2004 and 2015. In 1998, there was severe drought to extreme drought areas 45.25%, and there was drought risk area in the agricultural land use areas: extreme risk 22.196%, severe risk 26.707% of the agricultural land use area. In addition, the analysis of the SPI6 of October found that there was severe drought to extreme drought areas, representing more than 25% of the northern region for 2 years, namely 1993 and 2015. In 2015, there was severe drought to extreme drought areas 92.27%, and there was drought risk area in the agricultural land use areas: extreme risk 72.297%, severe risk 16.626% of the agricultural land use area.